Design of a Collaboration Document Management Information System for Internal Parties: Study of a Company Operating in the Field of Information and Communication Technology (ICT) Services and Telecommunication Networks in Indonesia - Annisa, Gizkha Qotrunnada; Ibrahim, Rohmat Nur (Electronic, Business, Management and Technology Journal, 2023)
Collaboration documents are necessary for various enterprises, diverse economic sectors, and academic institutions. Cooperation documents are essential in facilitating the collaboration between a company and its partners, making effective administration of these documents crucial. Companies benefit from collaboration with other companies since it allows them to mutually assist and support one another in achieving shared objectives, enhancing work efficiency and production. Companies and partners can expand their size by leveraging industrial connections, entering new markets, establishing new facilities, or introducing supplementary products. The management of collaboration document data collecting in the Digital Business and Technology division of an Indonesian company operating in information and communication technology (ICT) services and telecommunications networks is only partially automated. Computers are restricted to archiving records, resulting in frequently disorganized, damaged, or misplaced documents. This condition hinders employees' ability to locate the necessary papers for review, leading to delays in distributing documents to relevant parties and impeding the productivity and efficiency of the collaborative document management process. Hence, it is imperative to construct a proficient system that can facilitate the collaborative document management procedure, encompassing data administration, input, and storage. This study develops an information system that allows internal stakeholders to access documents as data housed in a web-based application conveniently. The collaborative document management information system uses the System Development Life Cycle (SDLC) method, specifically employing the waterfall model as the system development approach. The author employs the Unified Modeling Language (UML) model to analyze the system by generating the necessary diagrams, a programming language that utilizes PHP and MySQL databases. The system was tested using the white box method.